Surviving the ice: Northern refugia and postglacial colonization - Rowe, Kevin C. (National Academy of Sciences, 2004)
The contemporary distribution of biological diversity cannot be understood without knowledge of how organisms responded to the geological and climatic history of Earth. In particular, Quaternary expansions and contractions of glacial ice sheets are thought to have played an important role in shaping the distribution of biodiversity among current populations in the north-temperate region. In the central U.S., fossil and palynological data provide support for the maintenance of a large southeastern refuge during the last glacial maximum, and many temperate organisms are believed to have responded to glacial expansion by shifting their ranges to southern refugia and recolonizing northward to track the receding ice sheets. Thus, organisms are assumed to track favorable climates, and species ranges are expected to have shifted significantly. Here we present data from a deciduous forest vertebrate, the eastern chipmunk (Tamias striatus) in the central U.S., indicating the maintenance of multiple refugial sources as well as a southward expansion from a northern refugium. These results challenge the view that, during glacial maxima, organisms must have migrated south out of their ranges to track favorable climates.